2016
DOI: 10.1002/chin.201603182
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Regioselective and 1,2‐cis‐α‐Stereoselective Glycosylation Utilizing Glycosyl‐Acceptor‐Derived Boronic Ester Catalyst.

Abstract: Regioselective and 1,2-cis--Stereoselective Glycosylation Utilizing Glycosyl--Acceptor-Derived Boronic Ester Catalyst. -Various 1,2-anhydro glycosyl donors such as (I) react with diol glycosyl acceptors in the presence of a boron catalyst, derived in situ from the acceptor component and the boronic acid in the reaction medium. The procedure can be carried out under mild conditions in the absence of any additive and is also used for the synthesis of higher saccharides and an isoflavone glycoside. -(NAKAGAWA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The use of a boronic acid catalyst in 1,2-anhydro sugar activation was developed by the Toshima group in 2015. 577 It was found that a boronic acid catalyst would react with a partially unprotected glycosyl acceptor, leading to formation of a boronic ester that would perform as the actual catalyst in the glycosylations. Furthermore, it was found that the glycosylations of this novel method would lead to a very high selectivity for 1,2-cis-glycosides as well as being highly regioselective for one of the alcohol functionalities of the acceptor depending on the parent sugar (Scheme 95).…”
Section: Anhydro Sugars As Donorsmentioning
confidence: 99%
“…The use of a boronic acid catalyst in 1,2-anhydro sugar activation was developed by the Toshima group in 2015. 577 It was found that a boronic acid catalyst would react with a partially unprotected glycosyl acceptor, leading to formation of a boronic ester that would perform as the actual catalyst in the glycosylations. Furthermore, it was found that the glycosylations of this novel method would lead to a very high selectivity for 1,2-cis-glycosides as well as being highly regioselective for one of the alcohol functionalities of the acceptor depending on the parent sugar (Scheme 95).…”
Section: Anhydro Sugars As Donorsmentioning
confidence: 99%